2015
DOI: 10.1111/apt.13441
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the incidence and prevalence of eosinophilic oesophagitis in children and adults in population‐based studies

Abstract: Eosinophilic oesophagitis is an increasingly common diagnosis in North America and Europe. The population-based incidence and prevalence of eosinophilic oesophagitis vary widely across individual studies, probably due to variations in diagnosis and risk of bias of research. More prospective, large-scale, multicenter studies are needed to evaluate reported data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
161
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(205 citation statements)
references
References 57 publications
10
161
1
13
Order By: Relevance
“…A recent systematic review with meta-analysis on population-based studies reported a pooled incidence of 3.7/100,000 inhabitants/year and prevalence of EoE of 22.7 cases/ 100,000. 4 However, a remarkably high heterogeneity (I 2 99.9%) was observed for both incidence and prevalence across individual studies, likely due to research bias and variations in awareness and diagnostic criteria. With regards to this latter issue, available guidelines for EoE have systematically recommended ruling out a diagnosis of EoE in those patients with clinical, endoscopic and histological features characteristic of EoE who achieved remission on proton pump inhibitor (PPI) therapy.…”
Section: Introductionmentioning
confidence: 97%
“…A recent systematic review with meta-analysis on population-based studies reported a pooled incidence of 3.7/100,000 inhabitants/year and prevalence of EoE of 22.7 cases/ 100,000. 4 However, a remarkably high heterogeneity (I 2 99.9%) was observed for both incidence and prevalence across individual studies, likely due to research bias and variations in awareness and diagnostic criteria. With regards to this latter issue, available guidelines for EoE have systematically recommended ruling out a diagnosis of EoE in those patients with clinical, endoscopic and histological features characteristic of EoE who achieved remission on proton pump inhibitor (PPI) therapy.…”
Section: Introductionmentioning
confidence: 97%
“…Although EoE has been reported in all generations, the prevalence between children and adults is similar [13,25,26]. In adults, these conditions are two-or threefold more common in men, presenting primarily in young men ranging from 20 to 40 years of age [27].…”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, EGE is relatively common in the Asian population compared to the Western population [10][11][12]. A recent systematic review by Arias et al [13] revealed that the population-based prevalence of EoE was estimated at 2.3-56.3/100,000, with a combined prevalence of 22.7/ 100,000 and 0.28% in North American and European populations. As expected, the prevalence varies widely by the population investigated in each study.…”
Section: Epidemiologymentioning
confidence: 99%
“…En 2015 a été publiéel ap remière revue avec méta-analyse de l'épidémiologie de l'EoE basées ur des études de population [17], une approche moins biaiséeq ue les publications de cas de centres référents, qui ont une tendance inhérente à surévaluer les chiffres. Cette étude estime les cas d'EoE à 28,1/100 000 habitants (Intervalle de Confiance IC 95% :1 3-49)s io nc onsidère uniquement les 12 études présentant le moins de biais méthodologique [17]. Si on considère les USAe tl es 28 pays de l'UE, cela correspond à prèsd e2 50 000 cas d'EoE supposés.…”
Section: Epidémiologieunclassified